The suitability of the penal code in governing cyber child grooming in Malaysia / Nor Akhmal Hasmin - Hasmin, Nor Akhmal (2014)
The soaring usage of internet and social networking sites among children around the globe has given an adverse effect towards the children. The dark side of the internet has lead to child sexual exploitation and makes them as an easy prey for cyber predators since they are naïve and vulnerable creature. One of the alarming problems that concern children‟s online is being a victim of cyber child grooming. In Malaysia, there is neither specific legislation nor provision of law is available to prosecute paedophile that commit cyber grooming unlike our counterparts the United Kingdom, Australia and Singapore. Thus in the absent of such legal provision, no matter how grave the behaviour is it cannot be prosecuted unless it is formally prohibited by law. The only option available to prosecute cyber groomer is by resorting to traditional criminal law which is the Penal Code (Revised 1997) particularly Section 377E of the PC. But there is a concern on whether Section 377E of the PC is a suitable piece of legislation that can be used against cyber child groomer since it is an offence committed in a virtual world. This article aim to discuss and examine the suitability as well as the strengths and weaknesses of the Penal Code (Revised 1997) in governing online child grooming in Malaysia, with special reference to the current legal position in the United Kingdom, particularly Sexual Offences Act 2003 and Indecency with Children Act 1960